2016
DOI: 10.1039/c6ra01224h
|View full text |Cite
|
Sign up to set email alerts
|

Isatin thiosemicarbazone-blended polymer films for biomedical applications: surface morphology, characterisation and preliminary biological assessment

Abstract: Poly (methyl methacrylate) and polyurethane are polymers currently used for a range of biomedical applications. To modify their surface characteristics, biocompatibility and potentially reduce any related side effects the addition to the polymers of appropriate compounds has been investigated. Isatin thiosemicarbazone derivatives were synthesised and added to poly (methyl methacrylate) and polyurethane solutions before spin coating them on to a silica wafer. The resultant films were characterised with contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 43 publications
3
10
1
Order By: Relevance
“…The effect of ITSCs addition on advancing contact angles of EG and DIM follows a similar trend. This is in agreement with Mallinson et al, 26 who also observed an increase in hydrophobicity caused by the addition of isatin thiosemicarbazones to the polymer. As previously observed, 28 the effect of ITSC addition was much more dramatic in the case of PMMA lm formation, leading to highly hydrophobic surfaces, compared to the PU counterparts.…”
Section: Contact Angle Goniometrysupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of ITSCs addition on advancing contact angles of EG and DIM follows a similar trend. This is in agreement with Mallinson et al, 26 who also observed an increase in hydrophobicity caused by the addition of isatin thiosemicarbazones to the polymer. As previously observed, 28 the effect of ITSC addition was much more dramatic in the case of PMMA lm formation, leading to highly hydrophobic surfaces, compared to the PU counterparts.…”
Section: Contact Angle Goniometrysupporting
confidence: 92%
“…2, 3 and 4 for PMMA and PU lms blended together with ITSCs of 10, 100 and 500 mM. The AFM results show that the presence of ITSCs leads to formation of honeycomb structures and conrms our previous results 26 where it was shown that the lack of isatin derivative prevents the formation of pores. It is evident in the images that PMMA surfaces present a structured honeycomb arrangement with smaller pore diameter (280 AE 20 nm) than the PU lms (647 AE 54 nm).…”
Section: Atomic Force Microscopysupporting
confidence: 64%
“…This sample was found to be smoother (R a 9.8 ± 0.5 nm) than reported values from Bi et al [23]. (R a 35.8 ± 2.1 nm) though the substrate of SW in our studies was smoother (R a 0.15 ± 0.04 nm [61]) than the previously reported PTFE substrate (24.2 ± 1.3 nm) [23]. The dried protein films (Fig.…”
Section: Morphologycontrasting
confidence: 54%
“…Polymers were dissolved in THF (2% w/v). Consequently, the polymer solution was spin coated onto SW at 2,000 rpm for 30 s with a Laurell WS‐400‐6NPP spin coater as per Mallinson et al…”
Section: Methodsmentioning
confidence: 99%
“…The contact angles of water on all substrates used are presented in Table 1 35 are not affected by surface roughness. Table 1 Advancing contact angles of SW, PMMA and PU surfaces, n = 12.…”
Section: Contact Angle Goniometry and Surface Energiesmentioning
confidence: 99%